Family Money Problems - Michael S. Gutter (EDIS)
More money will not necessarily give you more happiness and contentment in life; but it can, provided you learn to manage it. This revised 6-page fact sheet is published by the UF Department of Family, Youth and Community Sciences, October 2011.